ANALISA KEBUTUHAN SILABUS BAHASA INGGRIS I MAHASISWA PERBANKAN SYARIAH BERBASIS ESP - Hilma Pami Putri (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2018)
English is a compulsory subject that must be studied by all students, including students of Islamic Banking. Various efforts have been made by the lecturers so that the learning of English is interesting and attractive to students, including designing learning for the specific purposes (English for Specific Purposes). However, students are still having difficulties and have not had a good output after learning it. In addition, the material provided seemed unattractive to students. It was because of the material provided is not based on students’ needs. This research is a descriptive research by using a qualitative approach to see students' needs for English.The data was taken in the form of qualitative data, the utterances from interviews with respondents. In addition, quantitative data was taken from questionnaires distributed to Islamic Banking students related to the needs analysis of the English syllabus. The questionnaire consisted of learning need which was divided into input, procedure, setting, teacher's role, and learners' role. From the results of the research, it was found that students have their own learning needs for the material taught to them. Their learning needs must be realized in the learning plan in order to the goals of English can be achieved well. Keywords: Learning Need, Need Analysis, ESP